2020
DOI: 10.1111/jce.14830
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of eliminating nonpulmonary vein triggers of atrial fibrillation and nonpulmonary vein premature atrial contractions at initial ablation for persistent atrial fibrillation

Abstract: Background The role of nonpulmonary vein (PV) triggers ablation in persistent atrial fibrillation (PEAF) was suggested but it is still under debate. Objectives We aimed to assess the effectiveness of non‐PV trigger‐targeted ablation for patients with PEAF. Methods Consecutive patients with PEAF undergoing catheter ablation (CA) between January 2015 and April 2017 were enrolled. Isoproterenol plus adenosine challenge was performed to provoke non‐PV triggers. Non‐PV triggers were defined as the trigger beats ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…The prevalence of non-PV trigger in AF ablation has been reported from 5% to 30%, however, non-PV trigger was detected in 35 among 751 sessions (4.7%) in this study and its rate was lower than the previous studies [ 12 , 23 , 24 ]. This may be related to the different induction manners such as the dose of drugs and the conditions of the patients [ 25 – 27 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of non-PV trigger in AF ablation has been reported from 5% to 30%, however, non-PV trigger was detected in 35 among 751 sessions (4.7%) in this study and its rate was lower than the previous studies [ 12 , 23 , 24 ]. This may be related to the different induction manners such as the dose of drugs and the conditions of the patients [ 25 – 27 ].…”
Section: Discussioncontrasting
confidence: 87%
“…The efficacy of linear-based ablation has been inconsistent among studies, which may be due to the different degree of atrial degeneration and the various mechanisms of AF in every patient [ 4 , 20 ]. In contrast, non-PV trigger ablation is a unique approach for each patient and could theoretically target every AF initiation [ 12 , 21 ]. We previously reported that ablation outcome in AF patients with non-PV triggers could be improved to the level of those without non-PV triggers, by selective mapping and ablation of non-PV triggers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 3 The complete elimination of the non-PV foci results in a significant improvement in terms of AF recurrence rates compared to those in patients in whom non-PV triggers were not completely eliminated. 4 , 5 This report shows that FAAM ablation was effective in eliminating the non-PV foci in patients with refractory AF. Therefore, AF recurrence was potentially improved.…”
Section: Discussionmentioning
confidence: 79%
“… 1 , 2 , 3 Non–pulmonary vein (PV) trigger elimination can improve the recurrence rate after paroxysmal and persistent AF ablation. 4 , 5 However, complete non-PV trigger elimination is challenging owing to difficulty in detecting the non-PV foci. We developed a novel visualization tool of the fractionated signal area in the atrial muscle (FAAM) map, which highlights the fractionated signal area using Lumipoint software in the ultra-high-density Rhythmia (Boston Scientific, Marlborough, MA) system and successfully identifies the non-PV foci.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the LVA approach group, the recurrence rate tended to be higher in patients without LVA (PVI alone) than in those with LVA (PVI plus LVA ablation). Although we acknowledge the limitation of our small sample size, an alternative ablation approach (e.g., non-PV trigger ablation) may be required to improve the outcome in PeAF patients without LVA [ 36 38 ]; at the very least, additional linear ablation or PVI alone according to the assessment of the LA voltage map might not be sufficient for PeAF patients without evidence of LVA or documented AFL.…”
Section: Discussionmentioning
confidence: 99%